DEVELOPMENT DIRECTIONS OF ENERGY SOURCES FOR UNMANNED AERIAL VEHICLE (UAV) - Marek MARCISZ; Jarosław KOZUBA; Kamil ULMAN (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of the research was to conduct a comprehensive analysis of various energy sources used in unmanned aerial vehicles (UAVs) and to determine which implemented energy sources are the best as well as what are the directions of energy source development. One hundred drone models were selected for the study, differing in their installed energy source, flight time, payload capacity, own weight, and application. The analyzed UAVs were powered by 6 energy sources: lithium polymer and lithium-ion batteries, combustion engines, hybrid drives, hydrogen fuel cells, and solar energy. The analysis covered both technical and economic, environmental, and operational aspects influencing the choice of a specific energy source. It allowed determining the best energy source for each of the 4 selected applications: military, monitoring, transport, and agriculture. An assessment of challenges related to the use and development of energy sources was also carried out, and areas where further research and innovation are necessary and essential were identified. It was found that in military applications, the development of UAV energy sources will focus on combustion engines and electric propulsion with lithium polymer batteries. In civilian applications (in transport, monitoring, and agriculture), it will be directed towards further research and improvement of hybrid drives and hydrogen fuel cells.